1995
DOI: 10.1111/j.1432-1033.1995.0710j.x
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Specific Carbohydrates into Eucalyptus gunnii Cells Increases their Freezing Tolerance

Abstract: The comparison of soluble sugar content in various cell lines of Eucalyptus gunnii exhibiting different freezing resistances revealed that the most resistant cell line contained the highest soluble sugar content. It was possible to increase the freezing resistance of the sensitive cell line by progressive exposure to low temperatures (acclimation). During the early stage of cold acclimation, an increase of soluble sugar concentration was observed in the cells confirming the correlation between freezing resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
2
12
0
2
Order By: Relevance
“…Contrary to the acclimation observed at 16 C for cell suspension culture or at 12 C for plantlets, this loss of frost tolerance after a direct culture at 13 C may be associated with the additional stressful effect of chilling and freezing. These results, in accordance with our previous data (Leborgne et al 1995a(Leborgne et al , 1995b, show that cold hardening of Eucalyptus cell suspension cultures occurs only after a very specific, progressive and gentle decrease in culture temperature. The rapid chilling program, when the cell suspension culture fails to cold acclimate, is appropriate for use as a negative acclimation control in these molecular studies, and the cold acclimation program can be used to study gene expression associated with an increase in freezing tolerance.…”
Section: Frost Tolerance and Gene Expression In Asupporting
confidence: 93%
See 1 more Smart Citation
“…Contrary to the acclimation observed at 16 C for cell suspension culture or at 12 C for plantlets, this loss of frost tolerance after a direct culture at 13 C may be associated with the additional stressful effect of chilling and freezing. These results, in accordance with our previous data (Leborgne et al 1995a(Leborgne et al , 1995b, show that cold hardening of Eucalyptus cell suspension cultures occurs only after a very specific, progressive and gentle decrease in culture temperature. The rapid chilling program, when the cell suspension culture fails to cold acclimate, is appropriate for use as a negative acclimation control in these molecular studies, and the cold acclimation program can be used to study gene expression associated with an increase in freezing tolerance.…”
Section: Frost Tolerance and Gene Expression In Asupporting
confidence: 93%
“…4A). This spectacular induced-frost tolerance, known as cold acclimation, has already been described for other Eucalyptus lines (Leborgne et al 1995b, Teulières et al 1989, Travert et al 1997. These results show that this biological system is well adapted to the study of gene expression associated with this strong adaptive response.…”
Section: Sxd1 Gene Structure and Genomic Organizationsupporting
confidence: 74%
“…In contrast, the cell suspension that was unable to acclimate did not accumulate soluble sugars in response to the same cold treatment. Also Leborgne et al (1995) made a comparison of soluble sugar content in various cell lines of E. gunnii exhibiting different freezing resistances revealed that the most resistant cell line contained the highest soluble sugar content.…”
Section: Resultsmentioning
confidence: 99%
“…Hekneby et al (2006), em leguminosas, também observaram que a aclimatação ao frio diminuiu o TL 50 e aumentou a concentração de carboidratos solúveis totais nas folhas de todas as espécies avaliadas. Correlação negativa entre o conteúdo de carboidratos solúveis e a temperatura letal de 50% (TL 50 ) também foi obtida em E. gunnii (LEBORGNE et al, 1995). Da mesma forma, Bravo et al (1998) Nas análises de prolina, identificou-se nos tecidos das plantas concentração média de 48,5 mg g -1 MS, a qual não foi influenciada pelo período de aclimatação (dados não apresentados).…”
Section: Valores Estimadosunclassified